Ecology of fear alters behavior of grizzly bears exposed to bear‐viewing ecotourism - Monica L. Short; Christina N. Service; Justin P. Suraci; Kyle A. Artelle; Kate A. Field; Chris T. Darimont (Ecology, 2024)
Humans are perceived as predators by many species and may generate landscapes of fear, influencing spatiotemporal activity of wildlife. Additionally, wildlife might seek out human activity when faced with predation risks (human shield hypothesis). We used the anthropause, a decrease in human activity resulting from the COVID‐19 pandemic, to test ecology of fear and human shield hypotheses and quantify the effects of bear‐viewing ecotourism on grizzly bear ( Ursus arctos ) activity. We deployed camera traps in the Khutze watershed in Kitasoo Xai'xais Territory in the absence of humans in 2020 and with experimental treatments of variable human activity when ecotourism resumed in 2021. Daily bear detection rates decreased with more people present and increased with days since people were present. Human activity was also associated with more bear detections at forested sheltered sites and less at exposed sites, likely due to the influence of habitat on bear perception of safety. The number of people negatively influenced adult male detection rates, but we found no influence on female with young detections, providing no evidence that females responded behaviorally to a human shield effect from reduced male activity. We also observed apparent trade‐offs of risk avoidance and foraging. When salmon levels were moderate to high, detected bears were more likely to be females with young than adult males on days with more people present. Should managers want to minimize human impacts on bear activity and maintain baseline age–sex class composition at ecotourism sites, multiday closures and daily occupancy limits may be effective. More broadly, this work revealed that antipredator responses can vary with intensity of risk cues, habitat structure, and forage trade‐offs and manifest as altered age–sex class composition of individuals using human‐influenced areas, highlighting that wildlife avoid people across multiple spatiotemporal scales.